2012
DOI: 10.1007/s11010-012-1405-9
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Epicatechin-induced calcium independent eNOS activation: roles of HSP90 and AKT

Abstract: Cardiovascular disease (CVD) is a leading determinant of mortality and morbidity in the world. Epidemiologic studies suggest that flavonoid intake plays a role in the prevention of CVD. Consumption of cocoa products rich in flavonoids lowers blood pressure and improves endothelial function in healthy subjects as well as in subjects with vascular dysfunction such as smokers and diabetics. The vascular actions of cocoa follow the stimulation of nitric oxide (NO). These actions can be reproduced by the administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 30 publications
1
33
1
Order By: Relevance
“…Mice treated with epicatechin alone (without exercise) have structural and metabolic changes in skeletal and cardiac muscle similar to those of mice undergoing exercise (60). Epicatechin alone and in combination with exercise has an additive effect to stimulate myocardial angiogenesis (70). Obese, diabetic db/db mice have prolonged lifespan, along with a decrease in markers of inflammation and LDL-cholesterol when treated with epicatechin (79).…”
Section: E682mentioning
confidence: 94%
See 1 more Smart Citation
“…Mice treated with epicatechin alone (without exercise) have structural and metabolic changes in skeletal and cardiac muscle similar to those of mice undergoing exercise (60). Epicatechin alone and in combination with exercise has an additive effect to stimulate myocardial angiogenesis (70). Obese, diabetic db/db mice have prolonged lifespan, along with a decrease in markers of inflammation and LDL-cholesterol when treated with epicatechin (79).…”
Section: E682mentioning
confidence: 94%
“…In human coronary artery endothelial cells, epicatechin phosphorylates and activates eNOS through Akt and a complex with HSP90 (70). Incubating human umbilical vein endothelial cells with cocoa extract inhibits angiotensinconverting enzyme activity and enhances NO production (64).…”
Section: E682mentioning
confidence: 99%
“…Many studies have reported the interaction of HSP90 and eNOS in various disease prevention (Ramirez-Sanchez et al, 2012;Vladic et al, 2011;Simet et al, 2013). It was reported that Hsp90 inhibitor was able to inhibit the eNOS and Hsp90 interaction and decrease the level of eNOS (Prangsaengtong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Of interest is the observation that under Ca 2+ -free conditions, EPI is uniquely capable of inducing NO production secondary to eNOS phosphorylation via AKT activation independently of the translocation of the enzyme from the plasmalemma. 6-6 However, no studies have examined the differential effects of EPI restricting its presence to the plasmalemma.…”
mentioning
confidence: 99%